Pengaruh Reward, Punishment dan Motivasi Kerja terhadap Kinerja Karyawan - Putra, Aditya; Liana, Lie (Universitas Batanghari, 2024)
Recently global era, such an extraordinary competitive power increasingly tight also broad. Human redources are among thise so crucial aspect of company. At successfully achieve the target. The target the following study was for analyzing the effect reward, punishment also working motivation at employee performance on PT Rapi Trans Logistik. The method of collecting samples used purposive sampling with the criteria permanent employee respondents who had work period at least 1 period. By using Roscoe's theory, the sample used was 86 respondents. The questionnaire was applied to obtain data. compiler tool, also SPSS 25 was used as a data testing tool. Data processing acquisition were at the declaration of informant explanations, variable explanations, validity trial acquisition, reliability trial acquisition, F trial acquisition, coefficient test results (R²) and hypothesis trial result. Discussion results show rewards has a positively also significantly impact at worker performance, punishment doesn’t having impact at worker performance, also working motivation has positively also significant impact at worker performance